OECD transfer pricing guidelines for multinational enterprises and tax administrators (OECD ParisFR, 2017)
Focuses on the application of the arm's length principle to evaluate the transfer pricing of associated enterprises, member countries and non-member) and MNEs by indicating ways to find mutually satifactory solutions to transfer pricing cases, thereby minimising conflict among tax administrations and between the tax administrations and MNEs thereby avoiding costly litigation.
Keywords: TAXATION